Bioinformatics study and cytotoxicity of several curcumin analogues in ovarian cancer - Retno Murwanti; Ritmaleni; Navista Sri Octa Ujiantari; I Made Rhamandana Putra; Aliffian Farhan Wahyudi; Vigha Ilmanafi Arifka (Current Research in Toxicology)
Ovarian cancer ranks as Indonesia’s third-leading cause of cancer-related death, emphasising the need for innovative treatments. This study combined bioinformatics, molecular docking, and experimental assays to tackle this challenge. We identified 166 ovarian cancer-related genes, with MYC standing out as a key target. Analysis of MYC mutations revealed prevalent alterations, though no significant survival differences were observed in patients with or without the mutations. Molecular docking pinpointed compound B155 as a promising MYC inhibitor. A preliminary cytotoxicity assay revealed compound B155′s notable activity, with an 87.19 % inhibition of cell viability at 50 μM. Most of the other curcumin analogues only caused more than 50 % inhibition at the same concentration. This result suggests alternative mechanisms of action, possibly antioxidant effects, warranting further exploration. In summary, this study unveiled MYC as a prime target for ovarian cancer treatment, with curcumin analogues like B155 showing potential. Nonetheless, the complex factors affecting cytotoxicity underscore the need for deeper investigation into these compounds’ mechanisms in ovarian cancer cells.